Pemanfaatan Infrastruktur Teknologi Informasi dalam Mendukung Layanan di BPJS Kesehatan Kedeputian Wilayah III - Malaya Aura Dini; Muhamad Kadafi (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the utilization of Information Technology Infrastructure in supporting services at BPJS Kesehatan Deputy Region III using qualitative methods. The main focus of this study is to understand how information technology infrastructure can improve the efficiency, effectiveness, and quality of services to participants. The qualitative methods used include in-depth interviews, observations, and analysis related to the implementation of information technology infrastructure at BPJS Kesehatan. The results of the study indicate that the utilization of management information systems, mobile applications, online portals, electronic queuing systems, and digital health services have significantly improved the accessibility and quality of services for participants. However, several challenges such as limited information technology infrastructure in remote areas, lack of training for staff, and data security issues still need to be addressed. This study also found several solutions to overcome these problems, including increasing investment in information technology infrastructure, continuous training for staff, and the implementation of more sophisticated security technology. Thus, the utilization of information technology infrastructure at BPJS Kesehatan Deputy Region III can be continuously improved to provide better and more equitable health services for all participants.